A nationwide, multicentric case-control study on vitiligo (MEDEC-V) to elicit the magnitude and correlates - Nilendu Sarma; Sayantani Chakraborty; Shital Poojary; B M Shashi Kumar; Lalit Kumar Gupta; Leelavathy Budamakuntla; Leishiwon Kumrah; Suchibrata Das; Ajay Govindrao Ovhal; Nirmal Kumar Mandal; Shuvankar Mukherjee; T V Anoop; et al. (Wolters Kluwer Medknow Publications, 2020)
Background: Vitiligo is an acquired, idiopathic, and common depigmentation disorder. The values of various epidemiologic parameters are often doubtful due to the methodological weaknesses of the studies. Aims: To elicit the magnitude of various epidemiological parameters and important correlates of vitiligo. Materials and Methods: Every vitiligo patient attending the outpatient department of medical colleges spread over most of the Indian states were examined over a period of 1 year. Various epidemiological and clinical variables were examined and compared with age and sex-matched controls (registered in the Clinical Trial Registry of India CTRI/2017/06/008854). Results: A total of 4,43,275 patients were assessed in 30 medical colleges from 21 Indian states. Institutional prevalence of vitiligo was 0.89% (0.86% in males and 0.93% in females,P <0.001). The mean age at presentation and mean age at onset were 30.12 ± 17.97 years and 25.14 ± 7.48 years, respectively. Head-neck was the most common primary site (n = 1648, 41.6%) and most commonly affected site (n = 2186, 55.17%). Most cases had nonsegmental vitiligo (n = 2690, 67.89%). The disease started before 20 years of age in more than 46% of cases. About 77% of all cases had signs of instability during the last 1 year. The family history, consanguinity, hypothyroid disorders, and depressed mood were significantly (P < 0.001) higher among the cases. First, second, and third-degree family members were affected in 269 (60.04%), 111 (24.78%), and 68 (15.18%) cases, respectively. Work-related exposure to chemicals was significantly higher among cases (P < 0.008). Obesity was less common among vitiligo cases [P < 0.001, odds ratio (OR) 0.78, 95% confidence interval (CI): 0.71-0.86]. Conclusion: This is one of the largest studies done on vitiligo in India. The prevalence of vitiligo was found to be 0.89% among hospital attendees. Prevalence of vitiligo was higher among females than in males and prevalence of family history, consanguinity, hypothyroid disorders were higher in vitiligo than among controls.